A humanized yeast-based toolkit for monitoring phosphatidylinositol 3-kinase activity at both single cell and population levels - Julia María Coronas-Serna; Teresa Fernández-Acero; María Molina; Víctor J. Cid (Microbial Cell, 2018)
Phosphatidylinositol 3-kinase (PI3K) is a key regulator of phosphoinositide-dependent signaling in mammalian cells and its dysfunction is related to multiple syndromes, including cancer. By heterologous expression in Saccharomyces cerevisiae, we have developed a humanized yeast system as a tool for functional studies on higher eukaryotic PI3K. Here we restrict PI3K activity in yeast to specific plasma membrane (PM) microdomains by fusing the p110α PI3K catalytic subunit to either a septin or an eisosome component. We engineered a Dual Reporter for PI3K (DRAPIK), useful to monitor activity on cellular membranes in vivo at a single-cell level, by simultaneous PM staining of the enzyme substrate (PtdIns4,5P2) with GFP and its product (PtdIns3,4,5P3) with mCherry. We also developed a sensitive FLUorescence by PI3K Inhibition (FLUPI) assay based on a GFP transcriptional reporter that is turned off by PI3K activity. This reporter system proved useful to monitor PI3K inhibition in vivo by active compounds. Such novel tools were used to study the performance of yeast PM microdomain-directed PI3K. Our results show that tethering heterologous PI3K to discrete PM domains potentiates its activity on PtdIns4,5P2 but different locations display distinct effects on yeast growth and endocytosis.